Fretting in complete contacts - the use of Williams’ solution - D. A. Hills; R. Flicek (Fracture and Structural Integrity)
Williams’ solution may be used to characterize the corners of ‘complete’ fretting contacts. Here we look at the practicalities of conducting fretting tests using a range of different kinds of apparatus and the kind of results they can reveal of practical relevance to establishing a fretting database.